Violences sexistes et sexuelles dans les sports : exemples de l’humour et de l’insulte - Stéphane Héas; Sylvain Ferez; Ronan Kergoat; Dominique Bodin; Luc Robène (Genre, Sexualité et Société)
Sport activities are ridden with violence. They range from words to acts perpetrated during and after the game. When they decide to limit sexism, racism and homophobia, the regulating authorities have a hard time to do so. In spite of measures aimed at promoting gender parity or reducing sex, race or ethnic discrimination, these moments are always problematic for minority persons. Beyond crudest, most explicit violence, we demonstrate the damages of insults and jokes. We detail them by offering a survey of the literature on the topic, supplemented by a recent survey of Brittany teenagers.